Efficacy of hepatitis B vaccination in patients awaiting liver transplantation in prophylaxis of de novo HBV-infection of a graft - V. Ye. Syutkin; O. I. Andreytseva; A. A. Saliyenko; A. V. Chzhao (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2010)
Aim of investigation. To estimate the efficacy of vaccination against hepatitis B in patients in the Waiting list for liver transplantation, in prophylaxis of de novo infection of a graft.Material and methods. Results of vaccination against hepatitis B in 41 patients with liver cirrhosis included into the Waiting list for orthotopic liver transplantation (OLT), and dynamics of HBV seromarkers in 72 patients before and after liver transplantation were analyzed.Results. Only in 9 (22%) of the patients vaccinated against hepatitis B, the level of anti-HBs to the moment of OLT was over 100 mMU/ml. At one third of patients who had no signs of HBV-infection in past history before operation, anti-HBc have been revealed after OLT. In half of them de novo graft HBV-infection developed. Presence of anti-HBs in blood serum of recipients prevented infection even if anti-HBc appeared after OLT.Conclusion. Vaccination against hepatitis B of patients with liver cirrhosis, etiologically not related to HBV-infection, standard doses of vaccine under the accelerated mode in most of the cases does not provide effective and sustained immunodefence and does not prevent development of graft HBV-infection de novo.